Inventory Management Optimization and Its Impact on Service Quality in Pharmacy Chains - Qardawi, Yusuf (Generasi Sains Indonesia, 2025)
This study examines the effect of inventory management optimization on service quality in pharmacy chains, focusing on operational efficiency and patient satisfaction. A quantitative approach with descriptive and explanatory design was applied. Inventory optimization employed ABC VED analysis to classify medicines and demand forecasting to predict stock requirements. Service quality was measured using the Customer Satisfaction Index (CSI) supported by SERVQUAL dimensions. Data were collected from pharmacy records and customer surveys over six months, divided into three months before and three months after optimization. The analysis compared stockout rates, average inventory holding costs, and CSI. Results indicate improvement after optimization. Stockout rates declined from 17 percent to 7 percent. Inventory holding costs decreased by approximately 27 percent, from USD 20,000 to USD 14,500. Meanwhile, CSI increased from 70 percent to 85 percent, reflecting better reliability and availability. These findings show that inventory optimization reduces inefficiencies while enhancing service quality. Inventory management optimization is essential for cost control and a driver of patient-centered service quality. By integrating ABC VED analysis and demand forecasting, pharmacy chains can achieve efficiency and customer satisfaction.